Uwarunkowania prawne odpowiedzialności za odesłania internetowe w Niemczech: [Legal framework of liability for hyperlinks in Germany] (Studia Prawnicze / The Legal Studies, 2010)
Trudno sobie wyobrazić, żeby prosty i niepozorny fragment kodu HTML, który w gruncie rzeczy składa się na odesłanie hipertekstowe, popularnie zwanym hiperlinkiem, mógł być tak ważny i nieodzowny dla funkcjonowania globalnej sieci, zwanej World Wide Web. Element strony internetowej, który po najechaniu na niego myszką sprawia, że standardowa strzałka kursora zamienia się w charakterystyczną „łapkę”, jest stałym elementem każdego portalu w sieci. Fenomen hiperlinku polega na jego prostocie i uniwersalności. Bez znaczenia jest bowiem, zarówno charakter informacji (fragment tekstu, plik muzyczny, zdjęcie, itp.), do której następuje odesłanie, jak też jej lokalizacja w obrębie globalnej sieci. Hiperlinki stanowią element spajający, łączący ze sobą pojedyncze komputery w coraz większe sieci, powodując, że Internet staje się faktycznie siecią globalną. Analizując problemy prawne związane z funkcjonowaniem hiperlinków, trzeba mieć zatem na uwadze wyjątkowe znaczenie tego narzędzia dla funkcjonowania Internetu. Z tej też racji szczególnie istotne jest, by nadmierne ograniczenia prawne w tym zakresie oraz zbyt restrykcyjna praktyka stosowania prawa nie odbiły się negatywnie na sprawności funkcjonowania Internetu, zaburzając pierwotne przeznaczenie hiperlinku, jako elementu konstrukcyjnego globalnej WWW. This article attempts to present the legal framework of liability for Hyperlinks in the German legal system. With the 1997 Teleservices act, this country was Europe’s first to adopt a complex regulation of electronic communication, including a special liability regime for Intermediary Service Providers, applicable horizontally to all types of legal claims. Still, even after a total revision of the law in 2001, required by the process of implementation of the 2000/31/ EC E-commerce Directive, and after a, maybe less revolutionary, transformation of the Teleservices act into the Telemedia act in 2007, which left the ISP liability section of the law unchanged, the problem of liability for hyperlinks has not been regulated directly. This doesn’t mean however, that the issue of liability of persons inserting hyperlinks into their web services poses a problem for German courts. This may have been the case under the original 1997 Teleservices act, when sometimes even very similar cases have been adjudicated differently by different courts. Paradoxically during that time the special ISP liability regime of the law was widely believed to be applicable to hyperlinks. The situation changed significantly after the revision in 2001, as the lawmaker, the doctrine and the judiciary unanimously stated the revised wording of the law, leaves no room for its direct application to hyperlinks. Worth mentioning here is the minority opinion, represented a.o. by Ulrich Sieber, claiming that, for certain types of hyperlinks (especially deep links provided automatically by search engines), an per anlogiam application of the Teleservices act may be possible. Nevertheless, with the new law the question as how to handle cases of alleged liability of hyperlink providers was entirely up to the court’s interpretation of general legal provisions. The practice of legal assessment hyperlinks, or the practice of inserting thereof into web services, has been widely developed and confirmed especially by German jurisprudence. The Federal Supreme Tribunal in its 2003 “Paperboy” ruling confirmed the general admissibility of linking as such, both in form of simple links and deep-links. Later on, in 2004, its “Schöner Wetten“ judgment the Tribunal introduced a procedure for testing particular cases of linking. According to the Tribunal, when assessing the legality of hyperlinks, first to consider is the possibility of so called “appropriation” (sich–zu–eigen–machen) of 3rd party information. Originating from press law, this legal institute was incorporated into the 1997 Teleservices act. After revision of the law in 2001 the institute of appropriation wasn’t transferred into the new wording of the law, nevertheless it continued to be applied by courts. With regard to hyperlinks, such “appropriation” of third party information may by assumed in situations when the ISP designs a hiperlink in a manner which may cause the average user to wrongly believe the information, the user is being directed to, was provided by the same ISP. This may often be the cas, when ISP’s own information is visually combined with 3rd party information, accessible by link (e.g. by using frames or in-line links). In such cases the ISP should be subject to liability just as if he were the content provider of such information. In cases of civil liability, when the test for “appropriation” of information falls out negative, courts should continue the assessment with regard to the possibility of “disturber liability” (Störerhaftung) of the ISP, according to section 1004 of the German Civil Code. According to the Federal Supreme Tribunal this type of liability prerequisites the existence of ISP’s obligation to monitor the information. By assessing if such obligation exists, the Tribunal noted, several factors need to be considered, which are: (a) the general context in which the hyperlink is used; (b) the purpose of the link, (c) the awareness of the ISP as to the illegality of the information directed to; and (d) if the ISP can be reasonably expected to recognize such illegality. The Tribunal also emphasized the importance of the time of linking, noting, that the ISP isn’t obliged to monitor a hyperlink once inserted, thus he can’t be made liable if a previously legal information (targeted by the link) has afterwards been changed.